Risk Management in the Agri-food Sector - Hrabrin Bachev (Contemporary Economics)
This paper incorporates the interdisciplinary New Institutional Economics in a comprehensive framework for analyzing risk management in the agri-food sector. First, it specifies the diverse types of agri-food risks (natural, technical, behavioral, economic, policy, etc.) and the modes of their management (market, private, public, and hybrid). Second, it defines the efficiency of risk management and identifies the factors (personal, institutional, dimensional, technological, and natural) of governance choice. Next, it presents stages in the analysis of risk management and the improvement of public intervention in the governance of risk. Finally, it identifies the contemporary opportunities and challenges for risk governance in the agri-food chain.